Effect of anagrelide on cardiac repolarization in healthy volunteers: a randomized, double‐blind, placebo‐ and positive‐controlled, thorough QT study. Issue 6 (22nd September 2014) - Troy, Steven; Parks, Virginia; Purkayastha, Jaideep; Gossart, Sophie; Goodman, Daniel B.; Achenbach, Heinrich; Armstrong, Martin; Martin, Patrick T.
Abstract The aim of this study was to assess the effect of low and high therapeutic doses of anagrelide (0.5 and 2.5 mg) on cardiac repolarization, measured by the QTcNi (individual correction) and QTcF (Fridericia's correction), compared with placebo and moxifloxacin 400 mg (positive control) in healthy subjects. In this randomized, double‐blind, crossover trial, 60 healthy volunteers were enrolled and randomized. Anagrelide 0.5 and 2.5 mg rapidly increased mean heart rate (HR) by 7.8 and 29.1 bpm respectively. For anagrelide 2.5 mg, the maximum time‐matched change (one‐sided 95% upper confidence bound) in mean QTcNi and QTcF was 13.0 msec (15.7 msec) and 10.0 msec (12.7 msec), respectively, at 1 h post dose. However, time‐matched changes in QTcNi and QTcF quickly decreased to <6 msec by 2 h post dose, despite high stable HR and high plasma concentrations of anagrelide and its active metabolite at these times. For anagrelide 0.5 mg, the maximum time‐matched change in mean QTcNi and QTcF was 7.0 msec (9.8 msec) and 5.0 msec (8.0 msec) respectively. No new safety concerns were reported. The increase in QTc interval met the definition for a positive thorough QT/QTc study only when HR was increasing rapidly, suggesting that the increased QTc may be related to the rapidly increasing HR rather than a direct effect of anagrelide plasma concentrations. However, the direct causal relationship of anagrelide on cardiac repolarization cannot be completely excluded, and caution is advised when treating patients with known risk factors for QT interval prolongation.